A Small Nation in the Turmoil of the Second World War : Money, Finance and Occupation (Belgium, its Enemies, its friends, 1939-1945) - Wee, Herman van der (Book collections on Project MUSE., 2009)
Based on intensive research in the archives of six countries, this monograph presents an in-depth analysis of Belgium's monetary and financial history during the Second World War. Exploring Belgium's financial and business links with Germany, France, The Netherlands, Great Britain, the United States, and the Grand Duchy of Luxembourg, the study focuses on the roles played in this complex wartime network by the Central Bank and private bankers in Brussels, by the Belgian government in exile in London, and by the Belgian minister plenipotentiary in New York. Among the many subjects arising in th.